Consumer buying behavior towards herbal-based products in Malaysia - Sharifuddin, Juwaidah; Ahmad Mazlan, Nurliyana; Rezai, Golnaz (Faculty of Agriculture, Jember University, 2012)
Remarkable growth in the use of herbal-based products has recently been noted. In Malaysia, herbal-based product consumption has gained increasing attention by consumers over the past several years. A variety of factors may influence this increasing trend of consumption including changes in lifestyle and belief in natural product. The aim of this paper is to identify the factors influencing the usage of herbal-based products. Data from four hundred and fifty respondents was collected by means of self-administered questionnaire, using the snowballing method. The findings revealed that 57.8% of total subjects have experience in buying herbal-based products. Research indicates that there are significant differences based on gender, education level and age on the use of herbal-based products. Other than the attribute and quality of products, the consumption of herbal-based products are also influenced by both lifestyle and personality of the consumers. With the growing demand of herbal-based product, Malaysians government as well as the industry players has to increase their effort in terms of research and consumer education with respect to herbal-based products. The results of this study will hopefully enlighten the marketers of herbal-based products and help them in devising appropriate marketing strategies in targeting consumers in Malaysia.